PENGARUH KOMPETENSI KOMUNIKASI INTERPERSONAL DALAM PEER TEACHING TERHADAP PERSEPSI REMAJA TENTANG KESIAPAN KEHIDUPAN BERKELUARGA - Salsabila Mustaan; AURELIUS ROFINUS LOLONG TELUMA; NOVITA MAULIDA (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2024)
The family life that each individual will face requires thorough preparation from adolescence to avoid failures in marital life later on. Therefore, through interpersonal communication in peer teaching, adolescents can be assisted in preparing for family life, as each individual transitions from adolescence to adulthood and enters married life. This research aims to determine the influence of interpersonal communication competence in peer teaching on adolescents' perceptions of family life readiness. This study employs a quantitative approach with a cross-sectional research design. The sample consists of adolescents affiliated with the GenRe NTB Forum, selected through purposive sampling. Data collection involves the use of questionnaires, and the data analysis technique includes validity testing, reliability testing, and hypothesis testing (simple linear regression analysis). The findings reveal that motivation has a more significant impact on the competence of interpersonal communication applied in peer teaching, consequently affecting adolescents' perceptions of family life readiness. The obtained significance value is 0.001 < 0.005, indicating the rejection of the null hypothesis. This suggests a positive influence of interpersonal communication in peer teaching on adolescents' perceptions of family life readiness within the GenRe NTB Forum.